Localization of TGF-β and TGF-β receptor in bovine term placentome and expression differences between spontaneous and induced parturition. Issue 11 (November 2015) - Hirayama, Hiroki; Koyama, Keisuke; Sawai, Ken; Fujii, Takashi; Naito, Akira; Fukuda, Shigeo; Kageyama, Soichi
Abstract: Introduction: Mechanisms of detachment of fetal membrane after parturition in cattle are poorly understood. Glucocorticoids trigger the initiation of parturition and may facilitate the placental maturation. We compared the disappearance of trophoblast binucleate cells (BNCs) and expression of transforming growth factor-β (TGFB) in term placentomes between spontaneous and induced parturition to investigate the influences of glucocorticoids on the placental maturity. Methods: Cows were delivered spontaneously (SP group) or after the administration of prostaglandin (PG) F2 α (PG group); dexamethasone, PGF2 α, and estriol (DEX group); and triamcinolone acetonide, PGF2 α, and betamethasone (BET group) and placentomes were collected immediately after parturition. The number of BNCs in hematoxylin and eosin stained section was examined. Protein localization and mRNA levels of TGFB and its receptor (TGFBR) were analyzed using immunohistochemistry and qRT-PCR, respectively. Results: TGFB1 is characteristically localized in the maternal septum in caruncle in contrast to TGFB2 and TGFB3, which are mainly found in cotyledonary villi and maternal epithelial cells. TGFBR1 and TGFBR2 colocalized in BNCs. The number of BNCs was lower in the SP group than in PG and DEX groups. mRNA levels of TGFB1, TGFBR1 and TGFBR2 in the SP group differed from PG and DEX groups. There was no difference between SP and BET groups in all analyses. Discussion: These results indicate that parturition inductions using PGF2 α or dexamethasone were not able to induce disappearance of BNCs and change of TGFB signaling. Results in the BET group suggest that investigation into types, dose, and dosage schedule of glucocorticoids may facilitate placental maturation. Highlights: TGFB isoforms are differentially localized in bovine term placentomes. TGFBR1 is specifically present in binucleate cells in bovine term placentomes. TGFB signaling is different between spontaneous and induced parturition. Glucocorticoids may facilitate changes in TGFB signaling in term placetomes.